Examining patient preferences in the treatment of rheumatoid arthritis using a discrete-choice approach - Alten, Rieke; Krüger, Klaus; Rellecke, Julian; Schiffner-Rohe, Julia; Behmer, Olaf; Schiffhorst, Guido; Nolting, Hans-Dieter (Patient preference and adherence, 2016)
Biological disease-modifying antirheumatic drugs (bDMARDs) used in second-line treatment of rheumatoid arthritis (RA) are administered parenterally. However, so-called targeted synthetic DMARDs (tsDMARDs) - developed more recently - offer alternative (ie, oral) administration forms in second-line treatment. Since bDMARDs and tsDMARDs can be regarded as equal in terms of efficacy, the present study examines whether such characteristics as route of administration drive RA patients' treatment choice. This may ultimately suggest superiority of some second-line DMARDs over equally effective options, at least according to RA-patient preferences. The current study assessed the importance of oral administration among other treatment characteristics differing between available second-line DMARDs for RA patients' preferences using a discrete-choice experiment (DCE). The DCE involved scenarios of three hypothetical treatment options in a -efficient design with varying levels of key attributes (route and frequency of administration, time till onset of drug effect, combination therapy, possible side effects), as defined by focus groups. Further patient characteristics were recorded by an accompanying questionnaire. In the DCE, patients were asked to choose best and worst options (best-worst scaling). Results were analyzed by count analysis and adjusted regression analysis. A total of 1,588 subjects completed the DCE and were eligible for final analyses. Across all characteristics included in the DCE, "oral administration" was most desired and "intravenous infusion" was most strongly rejected. This was followed by "no combination with methotrexate" being strongly preferred and "intake every 1-2 weeks" being strongly rejected. On average, levels of route of administration showed strongest influences on patients' decisions in post hoc bootstrapping analysis. According to the results, an oral DMARD that does not have to be combined with methotrexate and is not administered (only) every 1-2 weeks appears a highly favorable treatment option for patients with RA. DMARDs meeting these preferences may increase compliance and adherence in RA treatment.